Efficiency Analysis and Design Considerations of a Hysteretic Current Controlled Parallel Hybrid Envelope Tracking Power Supply - Babu, Ambily; Shivaleelavathi, B. G.; Yatnalli, Veeramma (Engineering, Technology & Applied Science Research, 2023)
This paper presents the realization of an Envelope Tracking Power Supply (ETPS), for a sinusoidal envelope input signal. A parallel hybrid topology is chosen for the implementation. In this topology, a voltage-controlled Class-AB linear amplifier stage and a current-controlled switching converter stage operate in parallel. A hysteretic current control scheme is employed to control the operation of the switching converter. Block-level implementation of the ETPS is done using Simulink 2017b, continuous mode simulation. Simulations are performed using a sinewave input envelope signal = 1.94+ 1.2 sin(ω∙t). The input frequency varied from 1MHz to 60MHz. As the input frequency is increased, the ETPS moves from the linear to the non-linear region of operation. During the transition, the slew rates of the load current and the switching current match at a particular input frequency of 2MHz while the efficiency peaks. The maximum obtained efficiency while tracking the sinewave input signal is 82.3%. The way the efficiency can be optimized by focusing on the matching of the slew rates of load and switching currents is explained. Also, an insight into the study of various circuit parameters and the trade-offs that the designer needs to consider while designing an ETPS, is provided.